Flood Control Analysis in the Jakarta Garden City Area, Cakung, East Jakarta - Rosadi Rosadi (Journal of Creative Power and Ambition (JCPA), 2026)
Land use changes in urban areas due to population growth and urbanization have reduced water catchment areas and increased surface runoff, resulting in inundation and flooding, including in the Jakarta Garden City area of Cakung, East Jakarta. This study aims to evaluate the performance of the existing drainage system and formulate more effective flood control measures. The analytical techniques used are hydrological and hydraulic analysis. The results of the analysis indicate that the capacity of the existing drainage system is not yet able to accommodate the planned flood discharge, resulting in inundation with a water level of approximately 0.4 m. The pump system is able to control the flood but requires a relatively long operating time to restore normal conditions, so flood control still relies on post-rain drainage. Therefore, it is necessary to increase channel capacity, optimize pump operation, and integrate with regional flood control systems such as the East Flood Canal to reduce inundation and accelerate receding times. This study shows that the effectiveness of the polder system is not only determined by pump capacity, but by the balance between inlet discharge, storage volume, and drainage operation time.